The coefficients of thermal expansion of boron arsenide (B12As2) between 25°C and 850°C - Whiteley, C. E.; Kirkham, M. J.; Edgar, James H. (My University, 2013)
The present investigation was undertaken to determine the coefficients of thermal expansion for the boron-rich compound semiconductor icosahedral boron arsenide (B[subscript 12]As[subscript 2]). B[subscript 12]As[subscript 2] powder was synthesized in a sealed quartz ampoule containing boron and arsenic heated to 1100 °C and 600 °C respectively for 72 hours. The lattice constants of the B[subscript 12]As[subscript 2] were measured by high temperature X-ray diffraction (HTXRD) between 25 °C and 850 °C. The average lattice coefficients of thermal expansion were calculated perpendicular and parallel to the <111> axis in the rhombohedral setting (equivalent to the a and c axes in the hexagonal setting) as 4.9×10[superscript −6] Kˉ¹ and 5.3×10[superscript −6] Kˉ¹, respectively. The average unit cell volumetric coefficient of thermal expansion was 15.0×10[superscript −6] Kˉ¹. Knowing these values can be useful in explaining the cracking that occurs in heteroepitaxial B[subscript 12]As[subscript 2] thin films and crystals precipitated from metal solutions upon cooling from their synthesis temperatures.
Keywords: Electronic materials; Semiconductors; Chemical synthesis; X-ray diffraction; Thermal expansion; B[subscript 12]As[subscript 2]